Effectivity of Growth Mindset-Based Learning on Elementary School Students' Achievement Motivation - Retno Fidyah Nuryani; Wahyu Sopandi; Yulianti Fitriani (MANDAILING GLOBAL EDUKASIA, 2026)
Fostering achievement motivation in elementary school students is critical to sustaining long-term academic engagement and resilience. While traditional educational practices often inadvertently reinforce a fixed mindset through rigid performance metrics, empirical research evaluating the structural impact of growth mindset-based interventions on young learners' intrinsic drive to achieve remains underrepresented. This study aims to examine the effect of growth mindset-based learning on elementary school students' achievement motivation. Employing a quantitative quasi-experimental design, this study involved 60 sixth-grade students, systematically assigned into an experimental class (n = 30, receiving growth mindset-based learning) and a control class (n = 30, receiving conventional instruction). Data on achievement motivation were gathered via a validated questionnaire and analyzed using descriptive statistical metrics alongside paired and independent sample t-tests. The empirical findings indicate that growth mindset-based learning exerts a highly positive and statistically significant effect on students' achievement motivation. The experimental group exhibited a substantial increase in mean motivation scores, rising from a pre-treatment baseline of 67.35 (low category) to an impressive 91.08 (very high category) post-treatment. In contrast, the control group’s post-test mean stagnated at 65.19 (low category), establishing the definitive pedagogical superiority of the growth mindset framework (p < 0.05). Consequently, growth mindset-based learning serves as a potent pedagogical alternative to overcome low achievement motivation in primary education. Beyond immediate psychological gains, these insights offer a scalable framework for curriculum designers to embed psychological resilience and effort-oriented praise into elementary instructional methodologies.